Documentation of medicinal plants used by Aneuk Jamee tribe in Kota Bahagia Sub-district, South Aceh, Indonesia - Adi Bejo Suwardi; MARDUDI MARDUDI; Zidni Ilman Navia; BAIHAQI BAIHAQI; MUNTAHA MUNTAHA (Society for Indonesian Biodiversity, 2021)
Abstract. Suwardi AB, Mardudi, Navia ZI, Baihaqi, Muntaha. 2021. Documentation of medicinal plants used by Aneuk Jamee tribe in Kota Bahagia sub-district, South Aceh, Indonesia. Biodiversitas 21: 6-15. Aneuk Jamee is one of the ethnic communities living along the western-south coast of Aceh. Various plants are used by the Aneuk Jamee tribe as a traditional medicine in treating diseases and disorders. The aim of this study was therefore to document the medicinal plants used by the Aneuk Jamee tribe in the Kota Bahagia sub-district, South Aceh, Indonesia. This study was conducted in three villages, namely Jombo Keupok, Seuneubok Kuranji, and Alur Dua Mas, Kota Bahagia subdistrict, South Aceh District, Aceh Province. This study was based on field surveys, plant collection, and interviews with the local people. Interviews were performed with 60 informants selected by using the Snowball Sampling technique. A total of 96 medicinal plant species, consisting of 50 families, have been documented to be used by the Aneuk Jamee tribe in the Kota Bahagia subdistrict. Fifty-nine (61%) species are cultivated and 37 (39%) species are wild. Leaves are the most widely used plant part (28%), followed by the fruit (19%), flower and tuber (6% each), seed (3%), and sap (2%) and the main mode of preparations are decoction (60%), followed by raw consumption (14%), smeared (10%), pounded (7%), dropped (6%), and affixed and squeezed (1% each). The high informant consensus factor (ICF=0.98) was assigned to the diseases of the blood and blood-forming organs and certain disorders involving the immune mechanism category.